Modified boron nitride-benzoxazine resin composite material as well as preparation method and application thereof
By synthesizing monomers containing alcohol hydroxyl groups in benzoxazine resin and chemically grafting with modified boron nitride to form a modified boron nitride-benzoxazine resin composite, the problem of insufficient thermal conductivity in the prior art is solved, and excellent thermal conductivity and thermal stability are achieved.
Patent Information
- Application Number
- CN202411879042.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-19
AI Technical Summary
In the prior art, the inherent thermal conductivity of benzoxazine resin is insufficient, making it difficult to meet the heat dissipation needs of electronic components. The poor compatibility of boron nitride and benzoxazine resin leads to uneven dispersion, hindering the improvement of thermal conductivity.
By performing Mannich condensation reaction of tyrosol, 1,10-diaminodecane and paraformaldehyde, a benzoxazine monomer containing alcohol hydroxyl groups was synthesized, and chemically grafted with modified boron nitride containing epoxy groups to form a modified boron nitride-benzoxazine resin composite.
Chemical grafting of modified boron nitride and benzoxazine monomer is achieved, which overcomes the problems of poor compatibility and uneven dispersion, and significantly improves the thermal conductivity and thermal stability of the composite material.
Smart Images

Figure CN119613648A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, and in particular to a modified boron nitride-benzoxazine resin composite material and a preparation method and application thereof. Background Art
[0002] In the fields of electronic information and aerospace, material selection and performance optimization have become key factors in promoting industry progress. Benzoxazine resin, as a thermosetting resin with excellent heat resistance, flame retardancy, solvent resistance, low dielectricity and dimensional stability, has been widely used in the manufacture of electronic packaging, copper clad laminates and aerospace materials.
[0003] As electronic components develop towards miniaturization and integration, the problem of heat dissipation becomes increasingly prominent, and higher requirements are placed on the thermal conductivity of materials. Although benzoxazine resin has demonstrated excellent performance in many aspects, its inherent thermal conductivity is still difficult to meet the urgent needs of current scientific and technological development and needs to be further improved. Boron nitride, as a material with excellent thermal conductivity, is regarded as a potential choice for improving the thermal conductivity of benzoxazine resin. However, the existing physical blending method is used to integrate boron nitride into benzoxazine resin. Due to the poor compatibility between the two, boron nitride is unevenly dispersed in benzoxazine resin and is easy to form agglomerates, which seriously hinders the effective improvement of the thermal conductivity of benzoxazine resin. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a modified boron nitride-benzoxazine resin composite material and a preparation method and application thereof. The present invention uses biomass tyrosol and 1,10-diaminodecane as raw materials for the first time, mixes with polyformaldehyde and then performs a Mannich condensation reaction to synthesize a benzoxazine monomer containing an alcoholic hydroxyl group, and reacts the benzoxazine monomer containing an alcoholic hydroxyl group with a modified boron nitride containing an epoxy group to obtain a modified boron nitride-benzoxazine resin composite material. The modified boron nitride-benzoxazine resin composite material obtained by the preparation method realizes the chemical grafting of the modified boron nitride and the benzoxazine monomer, overcomes the problems of poor compatibility and uneven dispersion caused by the physical blending method, and makes the modified boron nitride-benzoxazine resin composite material have excellent thermal conductivity.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] The first object of the present invention is to provide a method for preparing a modified boron nitride-benzoxazine resin composite material, comprising the following steps:
[0007] After tyrosol, 1,10-diaminodecane and polyformaldehyde are mixed, a Mannich condensation reaction is carried out to obtain a benzoxazine monomer containing an alcoholic hydroxyl group; wherein the molar ratio of tyrosol, 1,10-diaminodecane and polyformaldehyde is 2:1:4-4.4; during the Mannich condensation reaction, polyformaldehyde will be partially decomposed, so the amount of polyformaldehyde used is excessive to ensure that it fully reacts with tyrosol and 1,10-diaminodecane, thereby maximizing the generation of benzoxazine containing an alcoholic hydroxyl group.
[0008] The modified boron nitride containing epoxy groups is mixed with a benzoxazine monomer and then cured to obtain a modified boron nitride-benzoxazine resin composite material; during the curing process, the epoxy groups on the modified boron nitride undergo a ring-opening reaction and react with the alcoholic hydroxyl groups on the benzoxazine monomer, and react with the phenolic hydroxyl groups generated after the benzoxazine monomer is thermally opened to form an ether bond, thereby achieving chemical grafting of the modified boron nitride and the benzoxazine monomer to obtain a modified boron nitride-benzoxazine resin composite material; wherein the mass ratio of the modified boron nitride to the benzoxazine monomer is 5-30:70-95; when the mass of the modified boron nitride is less, the strength of the modified boron nitride-benzoxazine resin composite material is not significantly improved, while when the mass of the modified boron nitride is more, the content of the benzoxazine monomer is too little, so that the strength of the modified boron nitride-benzoxazine resin composite material decreases and the brittleness increases.
[0009] Preferably, the curing conditions are: first curing at 160°C, 170°C, and 180°C for 1h, respectively, and then curing at 190°C for 2h; wherein, compared with curing by gradually increasing the temperature at a heating rate, step-by-step curing can ensure that the modified boron nitride-benzoxazine resin composite material fully reacts at different temperature stages, promotes the formation and cross-linking of the internal structure of the modified boron nitride-benzoxazine resin composite material, and effectively avoids severe thermal stress during the curing process by controlling the temperature and time in stages, thereby helping to reduce defects inside the modified boron nitride-benzoxazine resin composite material and improve the overall performance and stability of the modified boron nitride-benzoxazine resin composite material.
[0010] Preferably, the mixing conditions of the modified boron nitride containing epoxy groups and the benzoxazine monomer are: stirring for 5 min to 30 min at 110° C. to 120° C.; wherein the benzoxazine monomer is melted and then mixed with the modified boron nitride containing epoxy groups, and the melting point of the benzoxazine monomer is higher than 110° C. Setting the temperature range of 110° C. to 120° C. ensures that the benzoxazine monomer can be effectively melted while avoiding the cross-linking reaction of the benzoxazine monomer caused by excessively high temperature, thereby preventing its viscosity from increasing abnormally.
[0011] Preferably, the conditions of the Mannich condensation reaction are: at 65°C to 78°C for 2h to 24h; wherein, when preparing the benzoxazine monomer, the temperature cannot exceed 120°C. Although high temperature can promote the reaction rate, the boiling point of ethanol is 78°C, which is relatively low, so 65°C to 78°C is selected.
[0012] Preferably, the modified boron nitride is prepared according to the following steps: placing boron nitride in a sodium hydroxide solution for hydroxylation to obtain hydroxylated boron nitride; adding a silane coupling agent and an organic solvent to the hydroxylated boron nitride for substitution reaction to obtain modified boron nitride.
[0013] Preferably, boron nitride is selected from hexagonal boron nitride; the thermal conductivity of hexagonal boron nitride is 34W / m·k, which has a thermal conductivity coefficient similar to that of stainless steel; in addition, hexagonal boron nitride does not react with weak acids and strong bases at room temperature, is slightly soluble in hot acids, and has good corrosion resistance to various inorganic acids, bases, salt solutions and organic solvents.
[0014] Preferably, the molar ratio of boron nitride to sodium hydroxide in the sodium hydroxide solution is 1:2-3.
[0015] Preferably, the mass volume ratio of hydroxylated boron nitride, silane coupling agent and organic solvent is 1 g: 0.5 mL to 2 mL: 5 mL to 10 mL; the stripping efficiency of boron nitride is the highest at this mass volume ratio.
[0016] Preferably, the conditions for the hydroxylation treatment are: hydroxylation treatment at 80°C to 100°C for 2h to 24h; and the conditions for the substitution reaction are: reaction at 90°C to 95°C for 6h to 12h.
[0017] Preferably, the organic solvent is selected from ethanol, ethyl acetate, N,N'-dimethylformamide or chloroform; more preferably, ethanol, which has good volatility and can be easily removed by distillation or evaporation in subsequent treatment, thereby reducing the generation of hazardous waste; in addition, ethanol, as an organic solvent, has low toxicity and has little impact on the human body and the environment.
[0018] Preferably, the silane coupling agent is KH560.
[0019] The second object of the present invention is to provide a modified boron nitride-benzoxazine resin composite material prepared by the above preparation method.
[0020] The third object of the present invention is to provide the use of the modified boron nitride-benzoxazine resin composite material in the preparation of thermal conductive materials.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention provides a method for preparing a modified boron nitride-benzoxazine resin composite material. First, tyrosol, 1,10-diaminodecane and polyformaldehyde are mixed and then subjected to a Mannich condensation reaction to synthesize a benzoxazine monomer containing an alcoholic hydroxyl group; wherein the molar ratio of tyrosol, 1,10-diaminodecane and polyformaldehyde is 2:1:4-4.4; then, the benzoxazine monomer is mixed with a modified boron nitride containing an epoxy group and then subjected to a curing treatment to obtain a modified boron nitride-benzoxazine resin composite material; wherein the mass ratio of the modified boron nitride to the benzoxazine monomer is 5-30:70-95.
[0023] In the curing process, the epoxy group on the modified boron nitride undergoes a ring-opening reaction, reacts with the alcoholic hydroxyl group on the benzoxazine monomer, and reacts with the phenolic hydroxyl group generated after the benzoxazine monomer is thermally opened to form an ether bond, thereby achieving chemical grafting of the modified boron nitride and the benzoxazine monomer, and obtaining a modified boron nitride-benzoxazine resin composite material with a cross-linked network structure. The modified boron nitride-benzoxazine resin composite material obtained by the preparation method achieves chemical grafting of the modified boron nitride and the benzoxazine monomer, overcomes the problems of poor compatibility and uneven dispersion caused by the physical blending method, and makes the modified boron nitride-benzoxazine resin composite material have excellent thermal conductivity.
[0024] 2. The preparation method of traditional benzoxazine resin is highly dependent on fossil resources, and a large amount of toxic solvents are used in the preparation process, which not only increases the environmental burden, but also seriously hinders the sustainable development of benzoxazine resin. In contrast, the present invention uses an environmentally friendly solvent, ethanol, when preparing benzoxazine monomers and modified boron nitride. In particular, in the process of preparing modified boron nitride-benzoxazine resin composite materials, biomass tyrosol and 1,10-diaminodecane are used as raw materials, and Mannich condensation reaction is carried out with polyformaldehyde to synthesize bio-based benzoxazine monomers, reducing dependence on fossil resources. In addition, the present invention also uses green solvent anhydrous ethanol when synthesizing benzoxazine monomers containing alcoholic hydroxyl groups, successfully avoiding the drawbacks of using toxic solvents in the traditional preparation of benzoxazine resins, thereby greatly reducing environmental pollution problems.
[0025] 3. The modified boron nitride-benzoxazine resin composite material prepared by the present invention has high thermal conductivity and excellent thermal stability; when the modified boron nitride addition amount is 30wt%, the thermal conductivity of the modified boron nitride-benzoxazine resin composite material can be increased to 0.75W / m·K, which is 139% higher than that of benzoxazine resin; in addition, the temperature of the modified boron nitride-benzoxazine resin composite material at 5wt% mass loss in a nitrogen atmosphere is 293°C, which is 22°C higher than that of benzoxazine resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1This is a synthetic route diagram of the benzoxazine monomers prepared in Examples 1 to 4.
[0027] Figure 2 This is a synthetic route for the modified boron nitride prepared in Examples 1 to 4.
[0028] Figure 3 This is the infrared characterization image of the benzoxazine monomer prepared in Example 1.
[0029] Figure 4 This is the hydrogen nuclear magnetic resonance spectrum of the benzoxazine monomer prepared in Example 1.
[0030] Figure 5 This is the DSC curve of the benzoxazine monomer prepared in Example 1.
[0031] Figure 6 The microscopic morphology of boron nitride and modified boron nitride, among which, Figure 6 Figure (a) shows the microscopic morphology of boron nitride. Figure 6 Figure (b) is the microscopic morphology of modified boron nitride.
[0032] Figure 7 This is the infrared characterization diagram of the hydroxylated boron nitride and modified boron nitride prepared in Example 1.
[0033] Figure 8 The infrared spectra of the modified boron nitride-benzoxazine resin composite materials prepared in Examples 1 to 4 and the benzoxazine resin prepared in Comparative Example 1 are shown.
[0034] Fig. 9 The fracture morphology diagrams of the modified boron nitride-benzoxazine resin composite materials prepared in Examples 1 to 4 and the benzoxazine resin prepared in Comparative Example 1, wherein: Fig. 9 Figure (a) is a fracture morphology of the benzoxazine resin obtained in Comparative Example 1. Fig. 9 Figure (b) is a fracture morphology of the modified boron nitride-benzoxazine resin composite material prepared in Example 1. Fig. 9 Figure (c) is a fracture morphology of the modified boron nitride-benzoxazine resin composite material prepared in Example 2. Fig. 9 Figure (d) is a fracture morphology of the modified boron nitride-benzoxazine resin composite material prepared in Example 3. Fig. 9 Figure (e) is a fracture morphology of the modified boron nitride-benzoxazine resin composite material prepared in Example 4.
[0035] Fig.10 The curing mechanism diagram of the modified boron nitride-benzoxazine resin composite material prepared in Examples 1 to 4 and the benzoxazine resin prepared in Comparative Example 1, wherein: Fig.10Figure (a) is a curing mechanism diagram of the benzoxazine resin prepared in Comparative Example 1. Fig.10 Figure (b) is a curing mechanism diagram of the modified boron nitride-benzoxazine resin composite material prepared in Examples 1 to 4.
[0036] Fig.11 The infrared thermal imaging results of the modified boron nitride-benzoxazine resin composite materials prepared in Examples 1 to 4 and the benzoxazine resin prepared in Comparative Example 1 are shown, wherein: Fig.11 Figure (a) is an infrared thermal image of the modified boron nitride-benzoxazine resin composite material prepared in Examples 1 to 4 and the benzoxazine resin prepared in Comparative Example 1. Fig.11 Figure (b) is an infrared thermal image temperature-time curve of the modified boron nitride-benzoxazine resin composite materials prepared in Examples 1 to 4 and the benzoxazine resin prepared in Comparative Example 1.
[0037] Fig.12 This is a graph showing the test results of thermal conductivity of the modified boron nitride-benzoxazine resin composite materials prepared in Examples 1 to 4 and the benzoxazine resin prepared in Comparative Example 1.
[0038] Fig.13 It is a TGA curve diagram of the modified boron nitride-benzoxazine resin composite material prepared in Examples 1 to 4 and the benzoxazine resin prepared in Comparative Example 1. DETAILED DESCRIPTION
[0039] The following will be combined with the data in the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Considering that in the prior art, with the development of science and technology, the requirements for the thermal conductivity of materials are increasing day by day, and the thermal conductivity of traditional benzoxazine resins is limited and it is difficult to meet the current needs. Although there are attempts to improve the thermal conductivity of benzoxazine resins by using boron nitride through physical blending, due to the poor compatibility of boron nitride with benzoxazine resins, boron nitride is unevenly dispersed in benzoxazine resins, making it difficult to effectively exert its thermal conductivity.
[0041] In view of the problems existing in the prior art, the present invention provides a method for preparing a modified boron nitride-benzoxazine resin composite material, comprising the following steps: mixing tyrosol, 1,10-diaminodecane and polyformaldehyde, and performing a Mannich condensation reaction to obtain a benzoxazine monomer containing an alcoholic hydroxyl group; wherein the molar ratio of tyrosol, 1,10-diaminodecane and polyformaldehyde is 2:1:4-4.4; mixing a modified boron nitride containing an epoxy group and a benzoxazine monomer, and performing a curing treatment; during the curing process, the epoxy group on the modified boron nitride undergoes a ring-opening reaction, reacts with the alcoholic hydroxyl group on the benzoxazine monomer, and reacts with the phenolic hydroxyl group generated after the benzoxazine monomer is thermally opened to form an ether bond, thereby achieving chemical grafting of the modified boron nitride and the benzoxazine monomer, and obtaining the modified boron nitride-benzoxazine resin composite material; wherein the mass ratio of the modified boron nitride to the benzoxazine monomer is 5-30:70-95.
[0042] The modified boron nitride-benzoxazine resin composite material obtained by the preparation method realizes the chemical grafting of modified boron nitride and benzoxazine monomer, overcomes the problems of poor compatibility and uneven dispersion caused by the physical blending method, and makes the modified boron nitride-benzoxazine resin composite material have excellent thermal conductivity.
[0043] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0044] Example 1
[0045] The preparation method of the modified boron nitride-benzoxazine resin composite material comprises the following steps:
[0046] S1. Synthesize benzoxazine monomers. The synthesis technology route is as follows: Figure 1 As shown:
[0047] 20g of tyrosol, 12.464g of 1,10-diaminodecane, 8.68g of paraformaldehyde and 200mL of anhydrous ethanol were added to a flask equipped with a magnetic pole, and the mixture was fully mixed using a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 78°C and reacted at a constant temperature for 12 hours. After the reaction was completed, the mixture was poured into a beaker and allowed to stand for cooling and crystallization, and then moved into a vacuum drying oven and dried at 50°C for 12 hours to obtain a benzoxazine monomer containing an alcoholic hydroxyl group, which was recorded as T-fa.
[0048] S2. Preparation of modified boron nitride, the synthesis technology route is as follows Figure 2 As shown:
[0049] Weigh 15.0g of hexagonal boron nitride and 60g of sodium hydroxide, add sodium hydroxide and deionized water into a beaker and mix evenly to prepare a 5mol / L sodium hydroxide aqueous solution. Then add the weighed hexagonal boron nitride and sodium hydroxide aqueous solution into a flask equipped with a magnet, use a heat-collecting constant temperature heating magnetic stirrer to fully mix them, and stir them at a constant temperature and high speed for 12h at 95°C. After the reaction is completed, wait for it to cool to room temperature, filter it repeatedly with a suction flask, and wash it with deionized water 5 times. Subsequently, place the solid in a vacuum drying oven and dry it at 60°C for 24h to obtain hydroxylated hexagonal boron nitride, recorded as BN-OH.
[0050] 8.0 g of BN-OH, 8 mL of KH-560 and 80 mL of anhydrous ethanol were added to a flask equipped with a magnet, and the mixture was fully mixed with a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 90° C. and stirred at constant temperature for 12 hours to obtain a mixed solution. After the stirring, the mixed solution was placed in a centrifuge tube, centrifuged at 3000 rad / min for 5 minutes, and then centrifuged at 5000 rad / min for 10 minutes to retain a white precipitate. The white precipitate was placed in a vacuum drying oven and dried at 50° C. for 12 hours to obtain a modified boron nitride containing an epoxy group, i.e., a modified boron nitride, which was recorded as KH-560 modified BN-OH.
[0051] S3. Preparation of modified boron nitride-benzoxazine resin composite material:
[0052] First, T-fa and modified boron nitride were weighed according to a mass ratio of T-fa to modified boron nitride of 95:5, added into a flask, and the mixture was fully mixed using a heat-collecting constant-temperature heating magnetic stirrer. The temperature was precisely controlled at 110°C, and the mixture was stirred continuously and evenly for 10 minutes to obtain a molten mixture.
[0053] Then, the molten mixture was placed in a vacuum drying oven, and uniformly added to the mold at 110°C. After evacuation until there were no bubbles, the mixture was moved into the mold after the temperature of the electric constant temperature blower dryer was raised to 160°C. The mixture was first cured at 160°C, 170°C, and 180°C for 1h, and then cured at 190°C for 2h. The mixture was cooled naturally to obtain a modified boron nitride-benzoxazine resin composite material, which was recorded as 5wt%.
[0054] Example 2
[0055] The preparation method of the modified boron nitride-benzoxazine resin composite material, wherein the mass ratio of T-fa to modified boron nitride in S3 is replaced from 95:5 to 90:10, comprises the following steps:
[0056] S1. Synthesize benzoxazine monomers. The synthesis technology route is as follows: Figure 1 As shown:
[0057] 20g of tyrosol, 12.464g of 1,10-diaminodecane, 8.68g of paraformaldehyde and 200mL of anhydrous ethanol were added to a flask equipped with a magnetic pole, and the mixture was fully mixed using a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 78°C and reacted at a constant temperature for 12 hours. After the reaction was completed, the mixture was poured into a beaker and allowed to stand for cooling and crystallization, and then moved into a vacuum drying oven and dried at 50°C for 12 hours to obtain a benzoxazine monomer containing an alcoholic hydroxyl group, which was recorded as T-fa.
[0058] S2. Preparation of modified boron nitride, the synthesis technology route is as follows Figure 2 As shown:
[0059] Weigh 15.0g of hexagonal boron nitride and 60g of sodium hydroxide, add sodium hydroxide and deionized water into a beaker and mix evenly to prepare a 5mol / L sodium hydroxide aqueous solution. Then add the weighed hexagonal boron nitride and sodium hydroxide aqueous solution into a flask equipped with a magnet, use a heat-collecting constant temperature heating magnetic stirrer to fully mix them, and stir them at a constant temperature and high speed for 12h at 95°C. After the reaction is completed, wait for it to cool to room temperature, filter it repeatedly with a suction flask, and wash it with deionized water 5 times. Subsequently, place the solid in a vacuum drying oven and dry it at 60°C for 24h to obtain hydroxylated hexagonal boron nitride, recorded as BN-OH.
[0060] 8.0 g of BN-OH, 8 mL of KH-560 and 80 mL of anhydrous ethanol were added to a flask equipped with a magnet, and the mixture was fully mixed with a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 90° C. and stirred at constant temperature for 12 hours to obtain a mixed solution. After the stirring, the mixed solution was placed in a centrifuge tube, centrifuged at 3000 rad / min for 5 minutes, and then centrifuged at 5000 rad / min for 10 minutes to retain a white precipitate. The white precipitate was placed in a vacuum drying oven and dried at 50° C. for 12 hours to obtain a modified boron nitride containing an epoxy group, i.e., a modified boron nitride, which was recorded as KH-560 modified BN-OH.
[0061] S3. Preparation of modified boron nitride-benzoxazine resin composite material:
[0062] First, T-fa and modified boron nitride were weighed according to a mass ratio of T-fa to modified boron nitride of 90:10, added into a flask, and the mixture was fully mixed using a heat-collecting constant-temperature heating magnetic stirrer. The temperature was precisely controlled at 110°C, and the mixture was continuously and evenly stirred for 10 minutes to obtain a molten mixture.
[0063] Then, the molten mixture was placed in a vacuum drying oven, and uniformly added to the mold at 110°C. After vacuuming until there were no bubbles, the mixture was moved into the mold after the temperature of the electric constant temperature blower dryer rose to 160°C. The mixture was first cured at 160°C, 170°C, and 180°C for 1h, and then cured at 190°C for 2h. The mixture was cooled naturally to obtain a modified boron nitride-benzoxazine resin composite material, which was recorded as 10wt%.
[0064] Example 3
[0065] The preparation method of the modified boron nitride-benzoxazine resin composite material, wherein the mass ratio of T-fa to modified boron nitride in S3 is replaced from 95:5 to 80:20, comprises the following steps:
[0066] S1. Synthesize benzoxazine monomers. The synthesis technology route is as follows: Figure 1 As shown:
[0067] 20g of tyrosol, 12.464g of 1,10-diaminodecane, 8.68g of paraformaldehyde and 200mL of anhydrous ethanol were added to a flask equipped with a magnetic pole, and the mixture was fully mixed using a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 78°C and reacted at a constant temperature for 12 hours. After the reaction was completed, the mixture was poured into a beaker and allowed to stand for cooling and crystallization, and then moved into a vacuum drying oven and dried at 50°C for 12 hours to obtain a benzoxazine monomer containing an alcoholic hydroxyl group, which was recorded as T-fa.
[0068] S2. Preparation of modified boron nitride, the synthesis technology route is as follows Figure 2 As shown:
[0069] Weigh 15.0g of hexagonal boron nitride and 60g of sodium hydroxide, add sodium hydroxide and deionized water into a beaker and mix evenly to prepare a 5mol / L sodium hydroxide aqueous solution. Then add the weighed hexagonal boron nitride and sodium hydroxide aqueous solution into a flask equipped with a magnet, use a heat-collecting constant temperature heating magnetic stirrer to fully mix them, and stir them at a constant temperature and high speed for 12h at 95°C. After the reaction is completed, wait for it to cool to room temperature, filter it repeatedly with a suction flask, and wash it with deionized water 5 times. Subsequently, place the solid in a vacuum drying oven and dry it at 60°C for 24h to obtain hydroxylated hexagonal boron nitride, recorded as BN-OH.
[0070] 8.0 g of BN-OH, 8 mL of KH-560 and 80 mL of anhydrous ethanol were added to a flask equipped with a magnet, and the mixture was fully mixed with a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 90° C. and stirred at constant temperature for 12 hours to obtain a mixed solution. After the stirring, the mixed solution was placed in a centrifuge tube, centrifuged at 3000 rad / min for 5 minutes, and then centrifuged at 5000 rad / min for 10 minutes to retain a white precipitate. The white precipitate was placed in a vacuum drying oven and dried at 50° C. for 12 hours to obtain a modified boron nitride containing an epoxy group, i.e., a modified boron nitride, which was recorded as KH-560 modified BN-OH.
[0071] S3. Preparation of modified boron nitride-benzoxazine resin composite material:
[0072] Firstly, T-fa and modified boron nitride were weighed in a mass ratio of 80:20 and added into a flask. The mixture was fully mixed with a heat-collecting constant temperature heating magnetic stirrer. The temperature was precisely controlled at 110°C and stirred continuously and evenly for 10 minutes to obtain a molten mixture.
[0073] Then, the molten mixture was placed in a vacuum drying oven, and uniformly added to the mold at 110°C. After vacuuming until there were no bubbles, the mixture was moved into the mold after the temperature of the electric constant temperature blower dryer rose to 160°C. The mixture was first cured at 160°C, 170°C, and 180°C for 1h, and then cured at 190°C for 2h. The mixture was cooled naturally to obtain a modified boron nitride-benzoxazine resin composite material, which was recorded as 20wt%.
[0074] Example 4
[0075] The preparation method of the modified boron nitride-benzoxazine resin composite material, wherein the mass ratio of T-fa to modified boron nitride in S3 is replaced from 95:5 to 70:30, comprises the following steps:
[0076] S1. Synthesize benzoxazine monomers. The synthesis technology route is as follows: Figure 1 As shown:
[0077] 20g of tyrosol, 12.464g of 1,10-diaminodecane, 8.68g of paraformaldehyde and 200mL of anhydrous ethanol were added to a flask equipped with a magnetic pole, and the mixture was fully mixed using a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 78°C and reacted at a constant temperature for 12 hours. After the reaction was completed, the mixture was poured into a beaker and allowed to stand for cooling and crystallization, and then moved into a vacuum drying oven and dried at 50°C for 12 hours to obtain a benzoxazine monomer containing an alcoholic hydroxyl group, which was recorded as T-fa.
[0078] S2. Preparation of modified boron nitride, the synthesis technology route is as follows Figure 2 As shown:
[0079] Weigh 15.0g of hexagonal boron nitride and 60g of sodium hydroxide, add sodium hydroxide and deionized water into a beaker and mix evenly to prepare a 5mol / L sodium hydroxide aqueous solution. Then add the weighed hexagonal boron nitride and sodium hydroxide aqueous solution into a flask equipped with a magnet, use a heat-collecting constant temperature heating magnetic stirrer to fully mix them, and stir them at a constant temperature and high speed for 12h at 95°C. After the reaction is completed, wait for it to cool to room temperature, filter it repeatedly with a suction flask, and wash it with deionized water 5 times. Subsequently, place the solid in a vacuum drying oven and dry it at 60°C for 24h to obtain hydroxylated hexagonal boron nitride, recorded as BN-OH.
[0080] 8.0 g of BN-OH, 8 mL of KH-560 and 80 mL of anhydrous ethanol were added to a flask equipped with a magnet, and the mixture was fully mixed with a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 90° C. and stirred at constant temperature for 12 hours to obtain a mixed solution. After the stirring, the mixed solution was placed in a centrifuge tube, centrifuged at 3000 rad / min for 5 minutes, and then centrifuged at 5000 rad / min for 10 minutes to retain a white precipitate. The white precipitate was placed in a vacuum drying oven and dried at 50° C. for 12 hours to obtain a modified boron nitride containing an epoxy group, i.e., a modified boron nitride, which was recorded as KH-560 modified BN-OH.
[0081] S3. Preparation of modified boron nitride-benzoxazine resin composite material:
[0082] Firstly, T-fa and modified boron nitride were weighed in a mass ratio of 70:30 and added into a flask. The mixture was fully mixed with a heat-collecting constant temperature heating magnetic stirrer. The temperature was precisely controlled at 110°C and stirred continuously and evenly for 10 minutes to obtain a molten mixture.
[0083] Then, the molten mixture was placed in a vacuum drying oven, and uniformly added to the mold at 110°C. After evacuation until there were no bubbles, the mixture was moved into the mold after the temperature of the electric constant temperature blower dryer was raised to 160°C. The mixture was first cured at 160°C, 170°C, and 180°C for 1h, and then cured at 190°C for 2h. The mixture was cooled naturally to obtain a modified boron nitride-benzoxazine resin composite material, which was recorded as 30wt%.
[0084] Example 5
[0085] The preparation method of the modified boron nitride-benzoxazine resin composite material comprises the following steps:
[0086] S1. Synthesis of benzoxazine monomer:
[0087] 20g of tyrosol, 12.464g of 1,10-diaminodecane, 8.68g of paraformaldehyde and 200mL of anhydrous ethanol were added to a flask equipped with a magnetic pole, and the mixture was fully mixed using a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 65°C and reacted at a constant temperature for 24h. After the reaction was completed, the mixture was poured into a beaker and allowed to stand for cooling and crystallization, and then moved into a vacuum drying oven and dried at 50°C for 12h to obtain a benzoxazine monomer containing an alcoholic hydroxyl group, which was recorded as T-fa.
[0088] S2. Preparation of modified boron nitride:
[0089] Weigh 15.0g of hexagonal boron nitride and 48.34g of sodium hydroxide, add sodium hydroxide and deionized water into a beaker and mix evenly to prepare a 5mol / L sodium hydroxide aqueous solution. Then add the weighed hexagonal boron nitride and sodium hydroxide aqueous solution into a flask equipped with a magnet, use a heat-collecting constant temperature heating magnetic stirrer to fully mix them, and stir them at a constant temperature and high speed for 24h at 80℃. After the reaction is completed, wait for it to cool to room temperature, filter it repeatedly with a suction flask, and wash it with deionized water 5 times. Subsequently, place the solid in a vacuum drying oven and dry it at 60℃ for 24h to obtain hydroxylated hexagonal boron nitride, recorded as BN-OH.
[0090] 8.0 g of BN-OH, 4 mL of KH-560 and 40 mL of anhydrous ethanol were added to a flask equipped with a magnet, and the mixture was fully mixed with a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 95° C. and stirred at constant temperature for 6 hours to obtain a mixed solution. After the stirring, the mixed solution was placed in a centrifuge tube, centrifuged at 3000 rad / min for 5 minutes, and then centrifuged at 5000 rad / min for 10 minutes to retain a white precipitate. The white precipitate was placed in a vacuum drying oven and dried at 50° C. for 12 hours to obtain a modified boron nitride containing an epoxy group, i.e., a modified boron nitride, which was recorded as KH-560 modified BN-OH.
[0091] S3. Preparation of modified boron nitride-benzoxazine resin composite material:
[0092] First, T-fa and modified boron nitride were weighed according to a mass ratio of T-fa to modified boron nitride of 90:10, and added into a flask. The mixture was fully mixed using a heat-collecting constant-temperature heating magnetic stirrer, the temperature was precisely controlled at 110°C, and the mixture was continuously and evenly stirred for 10 minutes to obtain a molten mixture.
[0093] Then, the molten mixture was placed in a vacuum drying oven, and then uniformly added into the mold at 110°C, and evacuated until there were no bubbles. After the temperature of the electric constant temperature blower dryer rose to 160°C, it was moved into the mold and cured at 160°C, 170°C, and 180°C for 1 h, respectively, and then cured at 190°C for 2 h. After naturally cooling, a modified boron nitride-benzoxazine resin composite material was obtained.
[0094] Example 6
[0095] The preparation method of the modified boron nitride-benzoxazine resin composite material is the same as the preparation steps of Example 1, except that it includes the following steps:
[0096] S1. Synthesis of benzoxazine monomer:
[0097] 20g of tyrosol, 12.464g of 1,10-diaminodecane, 9.55g of paraformaldehyde and 200mL of anhydrous ethanol were added to a flask equipped with a magnetic pole, and the mixture was fully mixed using a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 65°C and reacted at a constant temperature for 2h. After the reaction was completed, the mixture was poured into a beaker and allowed to stand for cooling and crystallization, and then moved into a vacuum drying oven and dried at 50°C for 12h to obtain a benzoxazine monomer containing an alcoholic hydroxyl group, which was recorded as T-fa.
[0098] S2. Preparation of modified boron nitride:
[0099] Weigh 15.0g of hexagonal boron nitride and 72.5g of sodium hydroxide, add sodium hydroxide and deionized water into a beaker and mix evenly to prepare a 5mol / L sodium hydroxide aqueous solution. Then add the weighed hexagonal boron nitride and sodium hydroxide aqueous solution into a flask equipped with a magnet, use a heat-collecting constant temperature heating magnetic stirrer to fully mix them, and stir them at a constant temperature and high speed for 2h at 100℃. After the reaction is completed, wait for it to cool to room temperature, filter it repeatedly with a suction flask, and wash it with deionized water 5 times. Subsequently, place the solid in a vacuum drying oven and dry it at 60℃ for 24h to obtain hydroxylated hexagonal boron nitride, recorded as BN-OH.
[0100] 8.0 g of BN-OH, 16 mL of KH-560 and 80 mL of anhydrous ethanol were added to a flask equipped with a magnet, and the mixture was fully mixed with a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 95° C. and stirred at a constant temperature for 2 h to obtain a mixed solution. After the stirring, the mixed solution was placed in a centrifuge tube, centrifuged at 3000 rad / min for 5 min, and then centrifuged at 5000 rad / min for 10 min to retain a white precipitate. The white precipitate was placed in a vacuum drying oven and dried at 50° C. for 12 h to obtain modified boron nitride, which was recorded as KH-560 modified BN-OH.
[0101] S3. Preparation of modified boron nitride-benzoxazine resin composite material:
[0102] Firstly, T-fa and modified boron nitride were weighed according to the mass ratio of T-fa to modified boron nitride of 80:20, and added into a flask. The mixture was fully mixed with a heat-collecting constant temperature heating magnetic stirrer, the temperature was precisely controlled at 110°C, and the mixture was stirred continuously and evenly for 10 minutes to obtain a molten mixture.
[0103] Then, the molten mixture was placed in a vacuum drying oven, and then uniformly added into the mold at 110°C, and evacuated until there were no bubbles. After the temperature of the electric constant temperature blower dryer rose to 160°C, it was moved into the mold and cured at 160°C, 170°C, and 180°C for 1 h, respectively, and then cured at 190°C for 2 h. After naturally cooling, a modified boron nitride-benzoxazine resin composite material was obtained.
[0104] Comparative Example 1
[0105] The preparation method of benzoxazine resin comprises the following steps:
[0106] S1. Synthesis of benzoxazine monomer:
[0107] 20g of tyrosol, 12.464g of 1,10-diaminodecane, 8.68g of paraformaldehyde and 200mL of anhydrous ethanol were added to a flask equipped with a magnetic pole, and the mixture was fully mixed using a heat-collecting constant temperature heating magnetic stirrer, and the mixture was heated to 78°C and reacted at a constant temperature for 12 hours. After the reaction was completed, the mixture was poured into a beaker and allowed to stand for cooling and crystallization, and then moved into a vacuum drying oven and dried at 50°C for 12 hours to obtain a benzoxazine monomer containing an alcoholic hydroxyl group, which was recorded as T-fa.
[0108] S2. Preparation of benzoxazine resin:
[0109] First, T-fa was weighed and added to a flask, and then placed in a vacuum drying oven. It was then evenly added to the mold at 110°C and evacuated until there were no bubbles. After the temperature of the electric constant temperature blower dryer rose to 160°C, it was moved into the mold and cured at 160°C, 170°C, and 180°C for 1h, respectively, and then cured at 190°C for 2h. The mixture was naturally cooled to obtain a benzoxazine resin, which was recorded as 0wt%.
[0110] observe Figure 3 It was found that the asymmetric characteristic peak of COC on the benzoxazine ring is located at 1229 cm -1 The symmetrical characteristic peak of COC is located at 1045 cm -1 In addition, the characteristic absorption peak of the benzoxazine ring is located at 928 cm -1 , which preliminarily proved that T-fa was successfully synthesized.
[0111] observe Figure 4 It was concluded that δ=1.30ppm was the methylene absorption peak of C-(CH2)6-, δ=1.56ppm was the methylene absorption peak of N-CH2-CH2-, δ=2.73ppm was the methylene absorption peak of N-CH2-, δ=2.78ppm was the methylene absorption peak of -CH2-OH, δ=3.82ppm was the methylene absorption peak on -CH2-CH2-OH, δ=3.98ppm was the methylene absorption peak on -CH2-N, δ=4.84ppm was the methylene absorption peak on O-CH2-N, and δ=6.74ppm~6.99ppm was the proton absorption peak on the benzene ring. The successful synthesis of T-fa was further verified by the hydrogen nuclear magnetic resonance spectrum.
[0112] observe Figure 5 It is concluded that 90.3℃ is the absorption peak temperature of T-fa, i.e. the melting temperature. There is only one exothermic peak during the curing process, with a temperature of 224.5℃, i.e. the curing peak temperature. The starting temperature of the curing process is 146℃, the peak temperature is 224.5℃, and the ending temperature is 247℃.
[0113] observe Figure 6 It was concluded that hexagonal boron nitride was in the shape of petals and lamellar stacking, and its volume was large, so it could not be used directly. However, the modified hexagonal boron nitride was in the shape of lamellar structure, and the lamellar spacing was increased, so it was easy to disperse.
[0114] observe Figure 7 It was found that the infrared curves of BN-OH and modified boron nitride both showed a significant peak at 1372 cm -1 The stretching absorption peak and 817cm -1 The bending vibration absorption peaks are the characteristic absorption peaks of hexagonal boron nitride. On the infrared curve of BN-OH, 3431cm -1 The peak is the hydroxyl peak, which proves that hydroxylated hexagonal boron nitride is successfully obtained. Further comparison shows that the infrared curve of modified boron nitride has an additional 2939cm -1 and 2836cm -1 Two significant characteristic peaks, corresponding to the vibration absorption peaks of methyl and methylene, respectively, indicate that the modified boron nitride containing epoxy groups was successfully prepared.
[0115] observe Figure 8 It was found that the benzoxazine ring was located at 1229 cm -1 The COC asymmetric characteristic peak is located at 1045cm -1 The COC symmetric characteristic peak and the peak at 928 cm -1The characteristic absorption peaks on the benzoxazine ring disappeared, proving that with the increase of curing temperature, the oxazine ring in the benzoxazine monomer underwent a ring-opening reaction. It was preliminarily judged that the modified boron nitride-benzoxazine resin composite material was successfully prepared.
[0116] observe Fig. 9 As shown in Figure (a), the fracture surface of the benzoxazine resin prepared in Comparative Example 1 is smooth, showing obvious brittle fracture. Fig. 9 Figure (b) and observations Fig. 9 Figure (c) shows that as the content of modified boron nitride increases, the distribution and amount of modified boron nitride in the benzoxazine monomer also increase; Fig. 9 Figure (e) shows that as the amount of modified boron nitride added increases, the lamellar structure of the modified boron nitride-benzoxazine resin composite material becomes more and more obvious. It is worth noting that no obvious agglomeration phenomenon was found in the modified boron nitride-benzoxazine resin composite materials prepared in Examples 1 to 4, indicating that the modified boron nitride has good dispersibility. This is because the epoxy group in the modified boron nitride undergoes a ring-opening reaction and reacts with the alcohol hydroxyl group on the benzoxazine monomer, and reacts with the phenolic hydroxyl group generated after the benzoxazine monomer is thermally opened to form an ether bond; compared with simple physical mixing or hydrogen bonding, the formation of ether bonds can effectively increase the interfacial compatibility between the modified boron nitride and the benzoxazine monomer.
[0117] observe Fig.10 It was concluded that the curing process of the benzoxazine monomer is that the oxazine ring of the benzoxazine monomer undergoes a ring-opening reaction to generate phenolic hydroxyl groups, forming a cross-linked network structure; the curing process of the modified boron nitride-benzoxazine resin composite materials prepared in Examples 1 to 4 is that the epoxy groups on the modified boron nitride undergo a ring-opening reaction, react with the alcoholic hydroxyl groups on the benzoxazine monomer, and react with the phenolic hydroxyl groups generated after the benzoxazine monomer is thermally opened to form ether bonds, so that the modified boron nitride is evenly dispersed in the benzoxazine monomer without agglomeration.
[0118] observe Fig.11It is concluded that when the content of modified boron nitride added increases, the surface temperature rise rate of the modified boron nitride-benzoxazine resin composite material slows down, and in the same heating time, the maximum temperature reached is quite different. When heated for 60s, the temperature of the benzoxazine resin prepared in Comparative Example 1 has reached 90.2°C. The surface temperatures of the modified boron nitride-benzoxazine resin composite material containing 20wt% modified boron nitride and the modified boron nitride-benzoxazine resin composite material containing 30wt% modified boron nitride are only 60.2°C and 53.8°C respectively; when the heating time reaches 120s, the surface temperatures of the modified boron nitride-benzoxazine resin composite material containing 20wt% modified boron nitride and the modified boron nitride-benzoxazine resin composite material containing 30wt% modified boron nitride are only 65.4°C and 59.1°C. This effectively proves that the modified boron nitride-benzoxazine resin composite material has a stronger thermal conductivity than the benzoxazine resin prepared in Comparative Example 1.
[0119] observe Fig.12 It is concluded that the thermal conductivity of the modified boron nitride-benzoxazine resin composite material with a modified boron nitride content of 5wt% is only 0.329W / m·K, which is not much different from the thermal conductivity of the benzoxazine resin obtained in Comparative Example 1, which is 0.3118W / m·K. When the content of modified boron nitride is 30wt%, the thermal conductivity of the modified boron nitride-benzoxazine resin composite material reaches as high as 0.7454W / m·K. When the content of modified boron nitride is relatively low, it will be widely dispersed in the benzoxazine monomer, and it is difficult to form an effective cross-linked structure with the benzoxazine monomer, so the change in thermal conductivity is not significant. However, as the content of modified boron nitride gradually increases, the modified boron nitride and the benzoxazine monomer begin to build a continuous heat conduction channel, and this change significantly improves the thermal conductivity of the modified boron nitride-benzoxazine resin composite material.
[0120] Table 1 TGA parameter table of modified boron nitride-benzoxazine resin composite materials prepared in Examples 1 to 4 and benzoxazine resin prepared in Comparative Example 1
[0121] Sample name <![CDATA[T di , unit ℃]]> <![CDATA[Y c , unit %]]> Comparative Example 1 271 9.8 Example 1 275 / Example 2 281 / Example 3 286 / Example 4 293 /
[0122] Note: di is the temperature at which the resin material loses 5wt% of its mass in a nitrogen atmosphere, Y c is the carbon residue rate of the resin material at 800°C in a nitrogen atmosphere, and / indicates that the carbon residue rate of the resin material at 800°C in a nitrogen atmosphere is 0.
[0123] observe Fig.13It is concluded that the thermal decomposition curve of the modified boron nitride-benzoxazine resin composite material is similar to the thermal decomposition curve of the benzoxazine resin prepared in Comparative Example 1, indicating that the introduction of modified boron nitride does not change the thermal decomposition mechanism of the benzoxazine monomer and maintains its inherent thermal degradation characteristics. Fig.13 The analysis shows that the carbon residue rate of the benzoxazine resin prepared in Comparative Example 1 at 800°C is 9.8%, indicating that it has a thermal stability basis. As the content of modified boron nitride increases, the thermal stability of the modified boron nitride-benzoxazine resin composite material is significantly improved. Specifically, the temperature of the modified boron nitride-benzoxazine resin composite material at 5wt% mass loss shows a trend of gradually increasing. When the content of modified boron nitride in the modified boron nitride-benzoxazine resin composite material reaches 30wt%, T di is 293°C. Compared with the benzoxazine resin prepared in Comparative Example 1, T di The increase is as high as 22°C, indicating that the addition of modified boron nitride improves the thermal stability of modified boron nitride-benzoxazine resin composites.
[0124] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a modified boron nitride-benzoxazine resin composite material, characterized in that: The following steps are involved: After mixing tyrosol, 1,10-diaminodecane and polyformaldehyde, a Mannich condensation reaction is carried out to obtain a benzoxazine monomer containing an alcoholic hydroxyl group; wherein the molar ratio of tyrosol, 1,10-diaminodecane and polyformaldehyde is 2:1:4-4.4; After the modified boron nitride containing epoxy groups is mixed with a benzoxazine monomer, a curing treatment is performed. During the curing process, the epoxy groups on the modified boron nitride undergo a ring-opening reaction and react with the alcoholic hydroxyl groups on the benzoxazine monomer, and react with the phenolic hydroxyl groups generated after the benzoxazine monomer is thermally opened to form an ether bond, thereby achieving chemical grafting of the modified boron nitride and the benzoxazine monomer to obtain a modified boron nitride-benzoxazine resin composite material; wherein the mass ratio of the modified boron nitride to the benzoxazine monomer is 5-30:70-95.
2. The method for preparing the modified boron nitride-benzoxazine resin composite material according to claim 1, characterized in that: The curing conditions are: first, curing at 160°C, 170°C, and 180°C for 1 hour respectively, and then curing at 190°C for 2 hours.
3. The method for preparing the modified boron nitride-benzoxazine resin composite material according to claim 1, characterized in that: The conditions of the Mannich condensation reaction are: reaction at 65°C to 78°C for 2h to 24h.
4. The method for preparing the modified boron nitride-benzoxazine resin composite material according to claim 1, characterized in that: Modified boron nitride is prepared according to the following steps: The boron nitride is placed in a sodium hydroxide solution for hydroxylation to obtain hydroxylated boron nitride; A silane coupling agent and an organic solvent are added to hydroxylated boron nitride to carry out a substitution reaction to obtain modified boron nitride.
5. The method for preparing the modified boron nitride-benzoxazine resin composite material according to claim 4, characterized in that: The boron nitride is selected from hexagonal boron nitride.
6. The method for preparing the modified boron nitride-benzoxazine resin composite material according to claim 4, characterized in that: The molar ratio of boron nitride to sodium hydroxide in the sodium hydroxide solution is 1:2-3.
7. The method for preparing the modified boron nitride-benzoxazine resin composite material according to claim 4, characterized in that: The mass volume ratio of hydroxylated boron nitride, silane coupling agent and organic solvent is 1g: 0.5mL~2mL: 5mL~10mL.
8. The method for preparing the modified boron nitride-benzoxazine resin composite material according to claim 4, characterized in that: The silane coupling agent is selected from KH-560.
9. A modified boron nitride-benzoxazine resin composite material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the modified boron nitride-benzoxazine resin composite material according to claim 9 in preparing a thermal conductive material.
Citation Information
Patent Citations
High-dielectric and high-thermal-conductivity heat-resistant composite dielectric
CN112300536A
Benzoxazine heat-conducting adhesive
CN116355564A
polybenzoxazine compositions with high thermal conductivity and method for their preparation
DE69818900D1
Surface treated boron nitride for forming a low viscosity high thermal conductivity polymer based boron nitride composition and method
US6160042A
Cited By
Self-repairing silicone rubber composite material and preparation method thereof
CN120519015A